A perspective towards a circular fashion design system - Melo, Beatrice (2019)
The current fashion design, production, and consumption system, known as ‘fast fashion’, is characterized by the manufacturing of low-quality garments in a short period of time carried out in developing countries. In parallel with the deficits in social responsibility and human rights, the prevailing ‘take-make-dispose’ system in the fashion industry is one of the main causes of environmental pollution that concerns the climate change, scarcity of natural resources and health problems for the living beings. Due to these facts, discussions on Circular Design strategies – for waste reduction, components recycling, and materials reuse – became increasingly relevant throughout the globe. This paper’s aspiration is to outline a perspective towards a Circular Fashion. The concept of the Design for Sustainability requires a holistic view throughout de-signing strategies as well as the establishment of cyclical systems for the production site. Notwithstanding, the efficient integration of social and cultural dimensions are vital for Sustainable Fashion’s triumph.